1997
DOI: 10.1094/phyto.1997.87.11.1111
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas translucens from Small Grains: Diversity and Phytopathological Relevance

Abstract: Sixty-eight presumptive Xanthomonas translucens strains isolated from 15 small grains or grass species were studied by pathogenicity tests on barley, bread wheat, oat, and bromegrass species, and also by AFLP, analysis of fatty acid methyl esters (FAME), and sodium dodecyl sulfate-polyacrylamide gel electrophoresis of protein extracts. The X. translucens strains were divided into three pathogenicity types based on differences observed on barley and bread wheat. Two unspeciated strains producing atypical sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 29 publications
5
69
0
Order By: Relevance
“…The advantages of this technique in characterizing microbial populations is the extensive coverage of the genome under study and that the complexity of the AFLP fingerprinting can be advantageously managed by adding selective bases to the primers during PCR amplifications (Vos et al 1995). For the bacterial genome, the AFLP method has been evaluated in microbial taxonomy (Vaneechoutte, 1996), in diversity studies of human pathogenic bacteria (Purcell & Hopkins 1996), and in characterizing plant pathogenic bacteria at the pathovar level (Bragard et al 1997, Janssen et al, 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this technique in characterizing microbial populations is the extensive coverage of the genome under study and that the complexity of the AFLP fingerprinting can be advantageously managed by adding selective bases to the primers during PCR amplifications (Vos et al 1995). For the bacterial genome, the AFLP method has been evaluated in microbial taxonomy (Vaneechoutte, 1996), in diversity studies of human pathogenic bacteria (Purcell & Hopkins 1996), and in characterizing plant pathogenic bacteria at the pathovar level (Bragard et al 1997, Janssen et al, 1996.…”
Section: Introductionmentioning
confidence: 99%
“…However, the power of rDNA-based protocols resides at a low phylogenetic or taxonomic level of resolution, which is valuable for classifying bacteria from the genus to even the kingdom level but which is insufficient to classify bacteria at the (sub)species level (Woese, 1987 ;Fox et al, 1992 ;Stackebrandt & Goebel, 1994 ;Hauben et al, 1997). Therefore, we postulated that rapid molecular genomic fingerprinting methods would be valuable, high-resolution alternative approaches to the classification of bacteria, especially on the species-, subspecies-or strain-specific level (Louws et al, 1994(Louws et al, , 1995Lin et al, 1996 ;Rademaker et al, , 1998Bragard et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Originally developed for plant breeding purposes, this technique essentially interweaves the speci¢city of whole-genome restriction fragment analysis and the selectivity of high-stringency PCR ampli¢cation without prior knowledge of primer target sequences [12]. The AFLP method is currently used in various ¢elds of microbiology including taxonomy [13,14], epidemiology [15,16], population ecology [17,18], and molecular evolution [19]. In the genus Aeromonas, it has been demonstrated that AFLP clustering and HG delineation are usually highly concordant and that AFLP data can be used for the construction of a reliable taxonomic framework in nomenclatural rearrangements [20] and new species descriptions [21].…”
Section: Introductionmentioning
confidence: 99%